Meditations on a Hobby Horse - Klerkx, Niels; CIAP, Hasselt; Pollers, Peter (Hasselt : CIAP vzw, 2015)
Bjarland, Sara ; Bosmans, Kasper ; De Meyer, Peter ; Forest, Anne ; Gilissen, Thomas ; Mazzarella, Thomas ; Otten, Femmy ; Van Simaey, Frederik
Meditations on a Hobby Horse, CIAP, Hasselt, 2/05-16/08/2015
boek